2005
DOI: 10.1111/j.1532-950x.2005.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 Techniques for Ureteroneocystostomy in Cats

Abstract: An extravesical ureteroneocystostomy technique using a simple interrupted pattern for anastomosis should be considered in cats undergoing renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 8 publications
(9 reference statements)
3
52
0
5
Order By: Relevance
“…For veterinary patients with ureteral stenosis, the traditional options typically include ureteral resection and anastamosis, ureteroureterostomy, ureteronephrectomy, or ureteroneocystostomy. 4,39 Postoperative ureteral strictures and ureteral leakage are the most concerning potential surgical risks, 40 and the difficulties of reimplantation and manipulation of the ureters in this particular proximal location were strongly considered. Obviously, ureteronephrectomy was not an option because of the bilateral nature of the disease in the dog of this report; even if the disease had been unilateral, this procedure would not be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…For veterinary patients with ureteral stenosis, the traditional options typically include ureteral resection and anastamosis, ureteroureterostomy, ureteronephrectomy, or ureteroneocystostomy. 4,39 Postoperative ureteral strictures and ureteral leakage are the most concerning potential surgical risks, 40 and the difficulties of reimplantation and manipulation of the ureters in this particular proximal location were strongly considered. Obviously, ureteronephrectomy was not an option because of the bilateral nature of the disease in the dog of this report; even if the disease had been unilateral, this procedure would not be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…68,10,11 Most of the experimental studies were done in laboratory animals and mainly involved bowel anastomoses. Sarin et al concluded that there was no significant increase in the incidence of leak or tissue damage with continuous sutures, although previous reports suggest that there can be vascular compromise with continuous suturing.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Although continuous sutures are more watertight compared with interrupted sutures, 5 the possibility of seeing the purse-string effect and tissue damage may be a concern. 68 We present the results of our retrospective analysis of the effects and outcome of continuous and interrupted sutures during laparoscopic pyeloplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Leakage of urine from the ureterotomy or anastomosis site has been reported in 2-18% of cases [9,17,18]. The risk of this complication is reduced with the experience of the surgeon.…”
Section: Complicationsmentioning
confidence: 99%
“…17 The ureteral wall is sutured to the mucosal layer of the bladder, starting at the crotch of the spatulated ureter.…”
mentioning
confidence: 99%